Estudio cuantitativo del dimorfismo sexual en restos óseos de la población de Medellín (2004)
ABSTRACT: The present study summarizes the description of sexual dimorphism found on metric characteristics in a contemporary sample of skeletons. The burial individual record had data on sex, age, cause of death and birthplace. The metric information corresponding to 44 skull variables, jaw and long bones (humerus, fémur and tibia) was recorded on each subject. The sample consisted of 70 mature individuals of known sex (20 women and 50 males) from a cemetery of the city of Medellín, Colombia. When the statistical comparison between sexes was performed by means of a one-way F test only six of the studied variables were not significant (p > 0.05) to determine sex. In accord with these results, hierarchical list of variables for sex determination aim is proposed. Moreover, it has been conducted a discriminant analysis in order to obtaining prediction equations for sex. Tibia variables yield the highest total percentage of correct classification. They achieved also a higher classification percentage in men that in women, as it is in the qualitative analysis.